jtgg 2021
DOI: 10.20517/jtgg.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

The association between genetic variants in HSD3B1 and clinical management of PCa

Abstract: Androgen is an important factor in the occurrence and progression of prostate cancer. The principal clinical strategy is androgen deprivation therapy (ADT). However, progression to castrate-resistant prostate cancer (CRPC) is almost inevitable to occur after ADT. One of the key mechanisms is the intertumoral synthesis of androgen where 3β-hydroxysteroid dehydrogenase isoenzyme-1 (3βHSD1, encoded by HSD3B1) catalyzes the ratelimiting step. A germline missense-encoding variant of HSD3B1(1245A>C, rs1047303) has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In the current study, the suggested polymorphisms, either G313A or C338T, may create a new potential protein with different structure and function which induces cellular carcinogenesis, resistance and apoptosis ( 57 ). Another suggestion is that the two polymorphisms may render HSD3B1 resistant to ubiquitination and proteasomal degradation, leading to a large amount of protein (DHT) accumulation in the cell, causing prostate tissue carcinogenesis as well as resistance to androgen-deprivation therapy in PC recurrence ( 57 60 ). The results suggested that these variants of the HSD3B1 steroidogenic enzyme gene could be a powerful new biomarker capable of identifying patients with aggressive disease who warrant early escalated therapy and in clinical management of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the suggested polymorphisms, either G313A or C338T, may create a new potential protein with different structure and function which induces cellular carcinogenesis, resistance and apoptosis ( 57 ). Another suggestion is that the two polymorphisms may render HSD3B1 resistant to ubiquitination and proteasomal degradation, leading to a large amount of protein (DHT) accumulation in the cell, causing prostate tissue carcinogenesis as well as resistance to androgen-deprivation therapy in PC recurrence ( 57 60 ). The results suggested that these variants of the HSD3B1 steroidogenic enzyme gene could be a powerful new biomarker capable of identifying patients with aggressive disease who warrant early escalated therapy and in clinical management of the disease.…”
Section: Discussionmentioning
confidence: 99%